The Ornithodoros hasei (Schulze, 1935) (Acari: Argasidae) species group in Argentina - Nava, Santiago (2007)
Six larvae of the genus Ornithodoros were collected in Rio Lavayén, approximately 1km north of Santa Rita, San Pedro Department (24º 28´S, 64º 48´W), Jujuy Province, Argentina, on three species of bats: Molossops temminckii (Burmeister, 1854) (Molossidae), Myotis albescens (E. Geoffroy, 1806) (Vespertilionidae) and Ornithodoros were collected in Rio Lavayén, approximately 1km north of Santa Rita, San Pedro Department (24º 28´S, 64º 48´W), Jujuy Province, Argentina, on three species of bats: Molossops temminckii (Burmeister, 1854) (Molossidae), Myotis albescens (E. Geoffroy, 1806) (Vespertilionidae) and Molossops temminckii (Burmeister, 1854) (Molossidae), Myotis albescens (E. Geoffroy, 1806) (Vespertilionidae) and (Burmeister, 1854) (Molossidae), Myotis albescens (E. Geoffroy, 1806) (Vespertilionidae) and Histiotus laephotis Thomas, 1916 (Vespertilionidae). All six larvae were identified as belonging to the Thomas, 1916 (Vespertilionidae). All six larvae were identified as belonging to the Ornithodoros hasei species group, whose members are common parasites of bats throughout the Neotropical Zoogeographic Region. This is the first record of the O. hasei species group in Argentina, and M. temminckii species group, whose members are common parasites of bats throughout the Neotropical Zoogeographic Region. This is the first record of the O. hasei species group in Argentina, and M. temminckii O. hasei species group in Argentina, and M. temminckii and H. laephotis are new hosts for this tick. Studies of the morphology, genetics and ecology of O. hasei across its vast range will be necessary in order to determine whether sibling species are present. H. laephotis are new hosts for this tick. Studies of the morphology, genetics and ecology of O. hasei across its vast range will be necessary in order to determine whether sibling species are present.